2012
DOI: 10.1159/000338804
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Response Regulator DegU Controls the Expression of Bacilysin in Plant-Growth-Promoting Bacterium Bacillus amyloliquefaciens FZB42

Abstract: The plant-growth-promoting-rhizobacteria Bacillus amyloliquefaciens FZB42 possess an enormous potential to synthesize a wide range of antimicrobial, antiviral and nematocidal compounds. One of them, the dipeptide antibiotic bacilysin, is synthesized by FZB42 during exponential growth. Here, we have demonstrated that bacilysin is positively regulated by the two-component response regulator DegU at the transcriptional level. In addition, ScoC (Hpr), a transition state regulator, negatively controlled expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…ScoC box2 and CodY box overlap in bacABCDEF operon upstream [86]. As recently, reported, the putative binding sites of both DegU and ScoC are found in the bacA promoter region in B. amyloliquefaciens [85].…”
Section: Research Papersupporting
confidence: 70%
See 1 more Smart Citation
“…ScoC box2 and CodY box overlap in bacABCDEF operon upstream [86]. As recently, reported, the putative binding sites of both DegU and ScoC are found in the bacA promoter region in B. amyloliquefaciens [85].…”
Section: Research Papersupporting
confidence: 70%
“…CcpA (catabolite control protein A) also positively regulates degU through binding directly to the degU upstream region [84]. DegU was shown to positively regulate bac operon as well as the monocistronic ywfH (bacG) at the transcriptional level in Bacillus amyloliquefaciens [85]. Another protein, the transition state regulator ScoC (Hpr), is known to negatively regulate protease production and sporulation.…”
Section: Research Papermentioning
confidence: 99%
“…Sequencing of the region next to the transposon insertion revealed that in mutant WY01, the RBAM_029230 gene was interrupted by the transposon insertion, while mutant RSpMarA2 harbored an interrupted degU gene, suggesting that synthesis of the antibacterial compound is strictly dependent on DegU. DegU, a global transcription regulator, activates the nonribosomal synthesis of the polyketide difficidin, the antifungal lipopeptide bacillomycin D, and bacilysin in FZB42 (23,24).…”
Section: Detection Of a Gene Cluster Involved In Bacteriocin Biosynthmentioning
confidence: 99%
“…As in other prokaryotes, two-component signal transduction systems of B. subtilis are important elements of the adaptive response to a variety of external conditions (9). A total of 35 two-component systems (TCS) were identified from the genome of strain BAB-1, including the biocontrol function-related TCS comP / comA (10), phoR / phoP (11), and degU / degS (12). Finally, we identified 86 transposons, 25 phage-like elements, and type III restriction modification systems in strain BAB-1 genome.…”
Section: Genome Announcementmentioning
confidence: 99%